AAS determination of cadmium in fruits and soils - Yaman, M; Dilgin, Y (Atomic Spectroscopy Press Ltd, 2002)
The Cd concentration in fruit samples was determined by using slotted tube atom trap (STAT)enrichment-flame atomic absorption spectrometry (FAAS) and graphite furnace atomic absorption spectrometry (GF-AAS). To identify the Cd phases most responsible for fruit-available Cd, the soil samples near the fruit plants were also analyzed for Cd by using various digestion and selective extraction reagents. The relation between the fruit-Cd levels and the Cd concentrations in the soil extracts was studied. Total Cd concentrations found in the soils was in the range from 60 to 420 mug kg(-1); none of them exceeded 0.5 mg kg(-1) which is the limit level set for anthropogenic impact. It was observed that the Cd concentrations of the cherry, strawberry, apple, and grape samples correlates to the Cd concentrations of the HNO3-H2O2 digestion of soil, Organically bound Cd in soils was found to be less than in carbonate-bound Cd. While the Cd concentration of the EDTA extracts in some soil samples was 94% of total Cd, it was found to be only 35% in other soils. To assess the accuracy of the total procedure, the results of STAT-enrichment-FAAS and GF-AAS were compared and acceptable agreement was found. The detection limit, defined as three times the standard deviation of the blank, was 0.03 mug L-1.
Keywords: Atomic-Absorption Spectrometry; Activated-Carbon Enrichment; Lead; Speciation; Vegetables; Water; Faas; Copper